DECONSTRUCTING THE PARADOX: WOMEN AS PERPETRATORS OF VIOLENT EXTREMISM IN MULTICULTURAL SPACES - Khafsoh, Nur Afni; Ilela, Jean. E.; Talakua, Rizard Jemmy (Universitas Islam Negeri Imam Bonjol Padang, 2025)
Violent extremism is no longer carried out by men against women. Now, this violence also involves women as actors, such as in cases of terror against the police and even calls for hatred towards other people or groups. This research aims to analyze the typology of violent extremism to explore the roots of the emergence of violent extremism that occurs in the context of women in Yogyakarta city. This research uses a qualitative approach through observation and interviews to collect data. Data analysis uses reduction, display, analysis, and conclusion.The results of the research show that cross-cultural conflicts between immigrants and native residents cause the three typologies of violent extremism at the micro level. In mezzo, there is fanaticism based on group, culture, or religion. At the macro level, the mobilization of women calls for hatred and rejection of different views and groups (Intolerance). The causes are inherent fanaticism, lack of knowledge about other groups, and low literacy and critical ability to obtain information. So, the tendency to act frontally in some cases comes to the fore.